TEACHING FINANCIAL LITERACY TO SCHOOLCHILDREN IS RELEVANT - Eshmamatova D. B.; Turaeva S. F. (Galaxy International Interdisciplinary Research Journal, 2022)
The relevance of this work is dictated by the fact that in the modern world of the development of society, accompanied by large-scale economic transformations, when the discrepancy between the financial knowledge of the population and the rapidly changing financial market becomes more and more obvious. The problems associated with financial literacy of the population are ensuring personal financial security. A financially literate person "should be able to monitor the state of personal finances, plan their income and expenses, form long-term savings and a financial "safety cushion" for unforeseen circumstances, have an idea of how to search for and use the necessary financial information, rationally choose financial services, live within their means, avoiding debts disproportionate to income and non-payments on them, to know and be able to defend their legal rights as a consumer of financial services, to be able to recognize signs of financial fraud, to be aware of the risks in the financial services market, to know and fulfill their duties as a taxpayer, to conduct financial preparation for life in retirement" and to be aware of the consequences of self-made decisions. And this stage of development, the authors believe that it is necessary to start from school.